2017
DOI: 10.1016/j.scib.2017.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Single crystalline CH3NH3PbI3 self-grown on FTO/TiO2 substrate for high efficiency perovskite solar cells

Abstract: a b s t r a c t ⇑ Corresponding authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 12 publications
2
64
0
Order By: Relevance
“…MAPbI 3 crystals were self-grown on FTO/TiO 2 substrates, as reported in our previous study 35,36 . The powder XRD (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MAPbI 3 crystals were self-grown on FTO/TiO 2 substrates, as reported in our previous study 35,36 . The powder XRD (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CH3NH3PbI3 crystals were self-grown on FTO/TiO2 substrates as reported in our previous study 20 (Figs. S1 and S2 in the Supplementary Information (SI)).…”
mentioning
confidence: 99%
“…83 Single-crystal MAPbI3-based PSCs, demonstrated almost no degradation in the open ambient at 30% humidity and 23 °C in the dark for a month, exhibiting superior stability than polycrystalline thin-film solar cells. 84 Moreover, even after being aged in the dark air for 1000 hours the PSCs device manifested 93% PCE of the initial PCE. 40…”
Section: Oxygen and Moisturementioning
confidence: 99%
“…15a). 39,84 Morphological investigations with atomic force microscopy (AFM) demonstrated that the topography of the device exhibited a smooth surface with a root mean square roughness of approximately 3.36 nm (Fig. 15b).…”
Section: P a G Ementioning
confidence: 99%
See 1 more Smart Citation